+0  
 
-1
120
2
avatar

-y-10=6x

5x+y=-10

solve by elimination

 Mar 21, 2022
 #1
avatar
0

 

-y-10=6x

5x+y=-10

solve by elimination 

 

Let's move some of those term around a bit, for clarity.  

 

–y – 10 = 6x         rearranges to             –6x – y = 10  

5x + y = –10         just leave it like it is      5x + y = –10  

                                                               ——————  

                          add the two together     –x        = 0   

 

so  x = 0  

 

substitute into an original equation     5(0) + y = –10   

 

so  y = –10  

.

 Mar 21, 2022
 #2
avatar+48 
0

Nice Job Guest!

 

^.itsfree

 Mar 24, 2022

33 Online Users

avatar